What is a gospel? - Watson, Francis (Wm. B. Eerdmans Publishing Co., 2022)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- Preface -- List of Abbreviations -- 1. What Is a Gospel? -- The Gospel Proclaimed and Written -- Defining the Gospel Genre -- 2. Seven Ways to Dispose of Judas Iscariot -- Judas and the Field of Blood (Gospel of Matthew) -- Judas Ruptured (Acts) -- Judas as Spectacle (Papias) -- Judas Harmonized (Apollinaris of Laodicea) -- Exit Judas (Gospel of John) -- No Judas (Gospel of Peter) -- Revelation and Exclusion (Gospel of Judas) -- 3. How Did Mark Survive? -- Mark as a Work in Progress -- Conserving Mark -- 4. Does Luke Need Q? -- A House Built on Sand? -- Luke and His Notebook -- Introducing the Inaugural Sermon -- 5. Q and the Logia -- Discovering the Logia -- Interpreting the Logia -- Competing Logia Theories -- The Politics of Q -- 6. Luke Rewriting and Rewritten -- The Rewritten Gospel (Luke) -- Rewriting as Displacement (Protevangelium of James) -- Rewriting as Falsification? (Marcion) -- Rewriting as Integration (Tatian) -- Rewriting as Coordination (Irenaeus) -- Divine Rewriting (Qur'an, Sura 3) -- 7. The Gospel of the Apostles -- The Epistula Apostolorum as Gospel -- The Gospel of the Apostles and the Gospel of John -- Redeploying Johannine Women -- Resolving Johannine Anomalies -- 8. Jesus versus the Lawgiver -- The Apocryphon of John -- The Acts of John -- The First Apocalypse of James -- The Marcionite Euangelion -- 9. Making Sense of the Betrayer -- The Confessor and the Opponent -- The Confessor as Opponent -- Judas's Passion -- 10. Reception as Corruption -- The Anonymous Gospel -- Tertullian's Failed Syllogism -- On the Originality (or Otherwise) of the Marcionite Gospel -- Appendix: Tertullian on Marcion's Antitheses -- 11. Toward a Redaction-Critical Reading of the Diatessaron Gospel -- Title and Sources -- The Gospel Prologue -- Zechariah the Priest -- Mary the Virgin.